Вуж юрт: повесть / Г. Красильников - Красильников Геннадий Дмитриевич (Удмуртское книжное издательство, 1956)
Экземпляры: КР (20011122) / Инвентарный номер: у7040 / Сис.шифр: С(Удм) / Авт.знак: К 78 / ГРНТИ: 17.82 / ББК: 84(2)